Hybrid B1+-shimming and gradient adaptions for improved pseudo-continuous arterial spin labeling at 7 Tesla - Meixner, Christian; Eisen, Christian; Schmitter, Sebastian; Müller, Max; Herrler, Jürgen; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To improve pseudo-continuous arterial spin labeling (pcASL) at 7T by exploiting a hybrid homogeneity- and efficiency-optimized (Formula presented.) -shim with adapted gradient strength as well as background suppression. Methods: The following three experiments were performed at 7T, each employing five volunteers: (1) A hybrid (ie, homogeneity-efficiency optimized) (Formula presented.) -shim was introduced and evaluated for variable-rate selective excitation pcASL labeling. Therefore, (Formula presented.) -maps in the V3 segment and time-of-flight images were acquired to identify the feeding arteries. For validation, a gradient-echo sequence was applied in circular polarized (CP) mode and with the hybrid (Formula presented.) -shim. Additionally, the gray matter (temporal) signal-to-noise ratio (tSNR) in pcASL perfusion images was evaluated. (2) Bloch simulations for the pcASL labeling were conducted and validated experimentally, with a focus on the slice-selective gradients. (3) Background suppression was added to the (Formula presented.) -shimmed, gradient-adapted 7T sequence and this was then compared to a matched sequence at 3T. Results: The (Formula presented.) -shim improved the signal within the labeling plane (23.6%) and the SNR/tSNR increased (+11%/+11%) compared to its value in CP mode; however, the increase was not significant. In accordance with the simulations, the adapted gradients increased the tSNR (35%) and SNR (45%) significantly. Background suppression further improved the perfusion images at 7T, and this protocol performed as well as a resolution-matched protocol at 3T. Conclusion: The combination of the proposed hybrid (Formula presented.) -phase-shim with the adapted slice-selective gradients and background suppression shows great potential for improved pcASL labeling under suboptimal (Formula presented.) conditions at 7T.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 7 Tesla; B1 shimming; pcASL; pTx; ultra-high field strengths; VERSE